Ex 4 va rog
Testul 3
Anexe:
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
4*radical(3)
Explicație pas cu pas:
x=2V3-2 = 2*(V3 - 1),
y=3+V3 = (V3)^2 + V3 = V3*(V3 + 1)
Atunci avem: x*y = 2*(V3 - 1) * V3*(V3 + 1) = 2V3*(V3 - 1)*(V3 + 1) =
= 2V3( (V3)^2 - 1^2) = 2V3 ( 3 - 1) = 2V3 * 2 = 4*V3.
Răspuns de
1
Răspuns:
Explicație pas cu pas:
xy=(2√3-2)(3+√3)=6√3+6-6-2√3=4√3
Alte întrebări interesante
Matematică,
8 ani în urmă
Studii sociale,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă